THE ABSENCE OF FEMALE REPRESENTATION IN FILM BAMBANG (2022): THE MALE GAZE AND LACANIAN OBJET PETIT A - Winasis, Brigitta; Suharjo, Rias Antho Rahmi (UI Scholars Hub, 2025)
The discourse of the male gaze in popular culture constructs ideal standards of femininity deemed attractive based on traits and physical appearances that are desired by men. The film Bambang (2022) is an example of media that employs the male gaze as an exclusive tool to present female characters. By applying the mise-en-scène analysis method in film studies, this article explores the problem of female characters representation that is reduced to be desired objects through the concepts of Laura Mulvey's male gaze and Lacanian objet petit a. This article finds that Bambang (2022) utilizes objectifying dialogue by the two main male characters to present and represent the female characters, while intended to create a humorous effect. The female characters are evaluated based on their appearances, regarded as “leftovers” to be contested, and depicted as objects of sexual desire for men. Although the female characters hold crucial roles in the story, their identities can only be imagined based on what the male characters describe. Despite their absence, they remain as desired objects for the male characters.